Assessment of the safety of Bacillus Calmette-Guérin vaccine administered orally to badgers (Meles meles). Issue 15 (5th April 2018) - Perrett, Simon; Lesellier, Sandrine; Rogers, Fiona; Williams, Gareth A.; Gowtage, Sonya; Palmer, Si; Dalley, Deanna; Davé, Dipesh; Weyer, Ute; Wood, Emma; Salguero, Francisco J.; Nunez, Alex; et al.
Highlights: Vaccinating badgers against TB is a tool under consideration to reduce the prevalence of bovine TB. Showing an oral vaccine is safe for badgers and the environment is mandatory for licensing. A high dose of BCG given orally to badgers was safe with occasional excretion of BCG in the faeces. BCG was not cultured from tissues and did not transmit to unvaccinated badgers. The risk of sensitising cattle due to BCG excreted from badgers is expected to prove extremely low. Abstract: European badgers ( Meles meles ) are a wildlife reservoir for Mycobacterium bovis ( M. bovis ) in parts of England, Wales and Ireland, constituting a potential source of tuberculosis (TB) infection for cattle. Vaccination of badgers against TB is one of the tools available for helping reduce the prevalence of bovine TB in badgers, made possible by the licensing in 2010 of Bacillus Calmette-Guérin (BCG) vaccine for intramuscular administration to badgers (BadgerBCG). However, practical limitations associated with administering an injected vaccine to wild animals make an oral, bait-delivered form of the vaccine highly desirable. Evaluation of the safety of oral BCG to badgers and the environment is a mandatory step on the road to licensing an oral vaccine. This study had the following objectives: (a) to determine whether adverse effects followed the oral administration of BCG vaccine to badgers; (b) to measure the quantity and frequency of BCG excreted in the faeces of vaccinated badgers; and (c) to assess whether there was evidence of the vaccine spreading to unvaccinated, 'sentinel' badgers sharing the same environment as vaccinated animals. We report here that the oral administration per badger of ≥6.4 × 10 9  cfu BCG, followed 14 days later by a single oral dose of ≥6.4 × 10 7  cfu BCG caused no adverse physical effects and did not affect the social behaviour and feeding habits of the vaccinated animals. BCG was cultured from the faeces of two of nine vaccinated animals (372 cfu/g and 996 cfu/g, respectively) approximately 48 h after the higher dose of BCG was administered and by one of the nine vaccinated animal (80 cfu/g) approximately 24 h after receiving the lower dose of BCG. We found no evidence for the transmission of BCG to unvaccinated, sentinel, badgers housed with the vaccinated animals despite the occasional excretion of BCG in faeces.